MicroRNA Control of Invasion and Metastasis Pathways - Sreekumar, Rahul; Sayan, Berna S.; Mirnezami, Alex H.; Sayan, A. Emre (Frontiers in Genetics, 2011)
Abstract: Despite recent advances, cancer remains a leading cause of death worldwide. In developed countries, the incidence of colorectal and breast cancer has been stable, but no improvement in prognosis has been observed if the patient presents with metastases at diagnosis. This fact highlights the importance of therapeutic approaches targeting cellular invasion and metastasis programmes as the next step in cancer treatment. During carcinoma progression a process called Epithelial-Mesenchymal Transition (EMT) results in enhanced invasion and motility which is directly linked with loss of epithelial polarity and epithelial junctions, migration permissive cytoskeleton alterations, and the acquisition of mesenchymal properties. The recent discovery of microRNAs (miRNAs) controlling key cellular pathways has opened a new era in understanding how EMT pathways are modulated. In this review, we classify EMT regulating proteins according to their cellular localization (membrane, cytoplasmic and nuclear), and summarize the current knowledge on how they are controlled by miRNAs and propose potential miRNAs for the transcripts that may control their expression.